Strengthening Global Security: Evaluating the Feasibility of a Nuclear-Armed UN Peacekeeping Force - Muhammad Younus; Achmad Nurmandi; Suswanta Suswanta; Abdul Rehman; Imelda Zamjanah Rahmawati; Ibrahim Shah (Journal of World Science, 2023)
This research paper examines the possibility of enhancing global security by establishing a United Nations (UN) peacekeeping force armed with nuclear weapons. Innovative approaches to conflict resolution and deterrence mechanisms are of the utmost importance in an era marked by geopolitical tensions and regional conflicts. This study's primary objective is to evaluate the viability and ramifications of providing UN peacekeepers with nuclear capabilities. To accomplish this objective, a multifaceted research strategy was employed. First, a comprehensive literature review was conducted to comprehend the historical context, current challenges, and potential benefits of a UN peacekeeping force armed with nuclear weapons. To assess the legal and ethical implications of such an initiative, an exhaustive analysis of international legal frameworks, disarmament agreements, and pertinent UN resolutions was conducted. The implications of this research are intricate and nuanced. A UN peacekeeping force armed with nuclear weapons could enhance deterrence and facilitate conflict resolution, but it raises significant concerns regarding proliferation risks, sovereignty, and global power dynamics. The discussion section delves into these findings, emphasizing the need for a balanced approach that carefully weighs the pros and cons and the importance of global cooperation in ensuring a secure and peaceful global order. This paper provides policymakers and academics contending with the evolving international security landscape with valuable insights.